PENGARUH KARAKTERISTIK INDIVIDU, KEPUASAN KERJA, MOTIVASI, DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT INDOKOM SAMUDRA PERSADA - Zayyan, Salma Fairus; Sayekti, Wuryaningsih Dwi; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The study aims to examine the employee’s personal characteristics, job satisfaction, motivation, work discipline, and performance at different sections as well as the influence of personal characteristics, work satisfaction, motivation and work discipline on employee performance.  This research was conducted at PT Indokom Samudra Persada, South Lampung Regency from December 2022 to January 2023.  The method utilized in the study was a survey method by employing 51 respondents who work for PT Indokom Samudra Persada as permanent employees from different sections, and their superiors.  The data in this study were analyzed by using quantitative descriptive analysis and multiple linear regression analysis. The results show that job satisfaction of PT Indokom Samudra Persada employees is in the satisfied category: employees have a good work motivation, discipline, and have a good performance. Individual characteristics including age, number of dependents, duration of service, and degree of education, and work satisfaction have no significant influence on employee performance. Meanwhile, motivation and work discipline significantly affect the performance of PT Indokom Samudra Persada employees. Key words: discipline, employee performance, individual characteristics, job satisfaction, and motivation.